PERANAN INDONESIA DALAM MEMBANTU PENANGANAN MASALAH ETNIS ROHINGYA DI MYANMAR (2014-2017) - Indah Nur Azizah (Universitas Komputer Indonesia, 2017)
Indonesia has a significant role as Indonesia helps to deal with ethnic Rohingya issues in Myanmar by politically engaging with the Myanmar government to discuss the issue, proposing solutions to stop violence and sending humanitarian aid to the Rohingyas both in Myanmar and in Bangladesh. Indonesia views positively with what the Myanmar government has done to solve its internal problems. This problem is certainly gradual to be solved. Indonesia as a country that has a very good relationship with Myanmar, always supports all the process within the government of Myanmar and respect the sovereignty of Myanmar.